2015
DOI: 10.3389/fmicb.2015.00608
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-up modeling approach for the quantitative estimation of parameters in pathogen-host interactions

Abstract: Opportunistic fungal pathogens can cause bloodstream infection and severe sepsis upon entering the blood stream of the host. The early immune response in human blood comprises the elimination of pathogens by antimicrobial peptides and innate immune cells, such as neutrophils or monocytes. Mathematical modeling is a predictive method to examine these complex processes and to quantify the dynamics of pathogen-host interactions. Since model parameters are often not directly accessible from experiment, their estim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(59 citation statements)
references
References 40 publications
(69 reference statements)
4
54
0
Order By: Relevance
“…We adapted our human whole-blood model (17,(28)(29)(30) and generated state-based models (SBMs) that simulate the immune reactions during infection in avian whole-blood samples. In order to cope with known differences between fungal and bacterial infection scenarios in avian blood, we implemented slightly different models for bacteria and fungi.…”
Section: Mathematical Modelingmentioning
confidence: 99%
See 1 more Smart Citation
“…We adapted our human whole-blood model (17,(28)(29)(30) and generated state-based models (SBMs) that simulate the immune reactions during infection in avian whole-blood samples. In order to cope with known differences between fungal and bacterial infection scenarios in avian blood, we implemented slightly different models for bacteria and fungi.…”
Section: Mathematical Modelingmentioning
confidence: 99%
“…In line with our previous studies on whole-blood infections in humans (17,(28)(29)(30), the experimental whole-blood infection assay was complemented by virtual infection modeling. By calibrating the virtual infection model to experimental data, the functional characteristics of the immune response in avian whole blood were quantified.…”
Section: Introductionmentioning
confidence: 99%
“…This analysis provides new insights into systemic host responses and may ultimately lead to the development of new anti-microbial regimens. Lehnert et al [130] constructed a bottom-up modeling approach, from a state-based model to an agent-based model, to simulate C. albicans infection in a human whole-blood model. The authors reported that polymorphonuclear neutrophils (PMN) cells are important effector cells in killing C. albicans in human blood.…”
Section: Computational Systems Biologymentioning
confidence: 99%
“…The authors reported that polymorphonuclear neutrophils (PMN) cells are important effector cells in killing C. albicans in human blood. The authors also surmised that a systemic medicine approach that utilizes the predictive power of virtual infection models will play a crucial role in infectious disease diagnosis in the future [130]. …”
Section: Computational Systems Biologymentioning
confidence: 99%
“…virus infects host), or on the population level (pathogen infections affecting a human population). Interactions among host and pathogen protein networks are called pathogen-host interactomes and investigating them may allow us to apprehend and be aware of the functioning of the host immune system and these important interacting proteins (IIPs) present in the host cell could be utilized as potential drug targets [2]. We have analyzed 3,905 interactions (edges) from 182 pathogens consisting of 1,188 proteins (nodes) that interact with 668 human proteins (nodes) from The Pathogen-Host Interaction Interaction Search Tool (PHISTO).…”
Section: Introductionmentioning
confidence: 99%